The Practice of Depreciation - Preinreich, Gabriel A. D. (Econometrica, 1939)
IN A PREVIOUS article1 I made a brief and incomplete survey of the theory of depreciation. In the present paper I discuss its practice. One obstacle to practical progress in this field is that mathematically trained minds are seldom well informed on what accountants actually do. The latter are therefore more often criticized for methods which they are not using than for those which they are. Even otherwise valuable contributions thus elicit opposition quite unnecessarily. The inappropriate antithesis tends to discredit the rest of the argument and prompts general retorts, for instance that is a of . . . determined by the practices of men.-Where accounting treatment diverges from economic theory, a similar divergence is likely to be found between economic theory and practice.2 Such an attitude, in turn, is not very helpful or progressive, even if the dangerous phrase tool of business is interpreted only in its best possible sense. In the article cited, I probably added to the already existing confusion by calling sample methods by certain names without proper qualification, although the same names are commonly applied to substantially different methods. The truth is that the familiar singlemachine formulae permit of different interpretations. To clarify the situation, the present paper identifies a greater number of methods unequivocally by developing their basic many-machine equations and comparing the results. References to practice and to individual writers' ideas are made wherever possible, before choosing a method which appears best suited to the practical needs of large enterprises and the investing public.